An online survey among convalescents 5 months post SARS-CoV-2 infection in China - Yalan Wang; Maoshun Liu; Yuanyuan Guo; Min Li; Peipei Guo; Wenjun He; Tian Ma; Peipei Liu; Yaxin Guo; Beiwei Ye; Jun Liu; Guizhen Wu (Elsevier, 2024)
The effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection persist months and years after recovery. We conducted an online survey to assess the health condition of convalescents approximately 5 months following the primary infection of SARS-CoV-2. The study recruited 5,510 individuals who were primary infected, 626 participants who had experienced reinfection, and 521 participants who were without infective history. The most common disorders after the primary infection group were fatigue (15.18 %), memory issue (13.13 %), post-exertional malaise (PEM, 11.68 %), and brain fog (11.29 %) at the time of survey. In addition, SARS-CoV-2 infection had an impact on the reproductive systems. In stepwise logistic regression analysis, smoking currently, with background diseases, and outpatient visits in the acute phase could be associated with moderate / severe disorders. Further analysis of different background diseases showed that allergic rhinitis, hyperlipidemia, cardiovascular disease, autoimmune diseases, neurological diseases, and asthma likely increased the risk of moderate/severe disorders. The probability of developing disorders of individuals with SARS-CoV-2 reinfection was higher before the secondary infection than uninfected people. Fatigue, PEM, muscle pain/spasms, chills, joint pain, excessive sweating at rest, headache / dizziness, sore throat or foreign body sensation in the throat, cough, expectoration, dry / painful / watery eyes, loss of appetite and constipation were associated with an increased risk of reinfection. It was essential to undertake further research with enhanced randomization in a larger sample in the community, and to strengthen the validation of the research conclusions. The findings of this study contribute to a deeper understanding of the health recovery process among coronavirus disease 2019 (COVID-19) convalescents. Moreover, the findings help identify characteristic health risk factors associated with convalescents and highlight the risk of moderate / severe disorders and reinfection. Furthermore, the findings also provide valuable guidance and reference for SARS-CoV-2 rehabilitation strategies and the prevention of reinfection, offering insights for scientific recommendations.